An Analysis of Clean Water Production, Distribution, and Utilization in Merauke Regency, 2021–2023 - Dhea Resky Apriana; Liberthy Mendila Tappo (Journal of Health Science and Pharmacy, 2025)
Background: Access to clean water is a fundamental indicator of public health and human well-being. In Papua Province, particularly in Merauke Regency, the provision of clean water services continues to face significant challenges due to limited infrastructure, difficult geographical conditions, dispersed settlement patterns, and constraints in technical and financial capacity. Objective: This study aims to describe the effectiveness of clean water production and distribution patterns in Merauke Regency, Papua Province, during the period 2021–2023, based on secondary data obtained from official statistical sources. Methods: A descriptive quantitative approach was employed using secondary data sourced from official provincial statistical records. The analysis focused on indicators of clean water production, distribution effectiveness, and utilization patterns over the study period. Data were systematically organized into tables and graphical presentations, and observed trends and patterns were interpreted narratively. Results: The findings reveal considerable fluctuations in clean water production and distribution. An increase in production was observed in 2022, followed by a decline in 2023. Distribution frequency varied across the study period, while water utilization was predominantly accounted for by household consumers. A notable discrepancy between production and utilization volumes suggests the presence of distribution inefficiencies, including potential non-revenue water losses. Conclusion: Clean water management in Merauke Regency remains constrained by complex structural and technical challenges. Strengthening governance frameworks, improving infrastructure, adopting monitoring and control technologies, and implementing inclusive service delivery approaches are essential to enhance the efficiency and equity of clean water distribution. Evidence-based policymaking and cross-sectoral collaboration are critical to achieving sustainable development targets in the drinking water sector.